2017
DOI: 10.29122/jbbi.v4i2.2589
|View full text |Cite
|
Sign up to set email alerts
|

POTENSI SENYAWA BIOAKTIF TANAMAN GENUS <i>Phyllanthus</i> SEBAGAI INHIBITOR REPLIKASI VIRUS HEPATITIS B

Abstract: In this research, simulations of molecular docking of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…The RMSD value is a benchmark for the docking algorithm to predict the protein-ligand conformation. The RMSD value is good if it is worth <2.0 (Firdayani et al, 2017). According to Pratama (2016), molecular tethering gives results close to experimental experiments if it has an RMSD value of <2.0.…”
Section: Resultsmentioning
confidence: 86%
“…The RMSD value is a benchmark for the docking algorithm to predict the protein-ligand conformation. The RMSD value is good if it is worth <2.0 (Firdayani et al, 2017). According to Pratama (2016), molecular tethering gives results close to experimental experiments if it has an RMSD value of <2.0.…”
Section: Resultsmentioning
confidence: 86%
“…The prevailing public conviction regarding the potency of the components present in medicinal plants and their associated properties has prompted a significant number of investigations to explore the advantages and viability of plant compounds as commercially viable pharmaceutical agents [5,60]. Recent studies have shown that Phyllantus niruri L. and Phyllantus urinaria L. can be used as HBV inhibitory agents [31,52]. Furthermore, the secondary metabolites in both Meniran species have active and significant antiviral and hepatoprotective benefits in their anti-inflammatory, antioxidant, and anticancer properties [29,48].…”
Section: Discussionmentioning
confidence: 99%
“…Firdayani et al [31] explained that the repanducinat acid contained in Meniran could inhibit viral replication during the formation of the protein shell. Furthermore, Jung et al [52] stated that pure corylaginous compounds significantly inhibit HBV DNA synthesis with HBsAg and HBcAg secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Food and Drug Administration (FDA) has approved two types of HBV drugs, namely immunomodulators/interferons (IFN-α-2b and peg-IFN-α-2a) and nucleoside analogues (Hu et al, 2019;Tseng et al, 2014), but long-term use of this drug can cause resistance and specific mutations in HBV so that the drug's efficacy decreases (Firdayani et al, 2017;. One of the efforts made is to use the capsid protein of HBV as a drug target because it has an important role in the HBV replication cycle (Chen et al, 2021;Liu, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%